2021
DOI: 10.1101/2021.02.08.430288
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Evolution of gene-rich germline restricted chromosomes in black-winged fungus gnats through introgression (Diptera: Sciaridae)

Abstract: Germline restricted DNA has evolved in diverse animal taxa, and is found in several vertebrate clades, nematodes, and flies. In these lineages, either portions of chromosomes or entire chromosomes are eliminated from somatic cells early in development, restricting portions of the genome to the germline. Little is known about why germline restricted DNA has evolved, especially in flies, in which three diverse families, Chironomidae, Cecidomyiidae, and Sciaridae exhibit germline restricted chromosomes (GRCs). We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 69 publications
0
14
0
Order By: Relevance
“…This theory contains some testable predictions about GRC evolution, namely that they are expected to have evolved after the divergence of Sciaridae from their sister clade (as this family does not exhibit paternal genome elimination) and that they evolved from the X chromosome and therefore would be expected to contain genes derived from this chromosome. However, a recent study found that GRCs in the Sciarid B. coprophila do not bear significant homology to the X chromosome in this species, and instead have homologous regions to all chromosomes in the core genomes, suggesting that in Sciaridae, at least, the GRCs do not seem to have evolved from the X chromosome ( Hodson et al. 2021 ).…”
Section: Origin and Evolution Of Grcs In Dipteramentioning
confidence: 81%
See 2 more Smart Citations
“…This theory contains some testable predictions about GRC evolution, namely that they are expected to have evolved after the divergence of Sciaridae from their sister clade (as this family does not exhibit paternal genome elimination) and that they evolved from the X chromosome and therefore would be expected to contain genes derived from this chromosome. However, a recent study found that GRCs in the Sciarid B. coprophila do not bear significant homology to the X chromosome in this species, and instead have homologous regions to all chromosomes in the core genomes, suggesting that in Sciaridae, at least, the GRCs do not seem to have evolved from the X chromosome ( Hodson et al. 2021 ).…”
Section: Origin and Evolution Of Grcs In Dipteramentioning
confidence: 81%
“…1971 ). Yet, recent genomic evidence suggests that there is likely very little recombination between the two GRCs in B. coprophila ( Hodson et al. 2021 ).…”
Section: Reproduction and Grcsmentioning
confidence: 99%
See 1 more Smart Citation
“…In these groups we may expect female-beneficial variants to be enriched on the autosomes, whilst male-beneficial ones would be expected to be overrepresented on the sex chromosomes, regardless of assumptions about dominance, making this a more straightforward prediction than between autosomes and sex chromosomes in conventional eumendelian systems (Rice 1984; Patten 2019). In addition to X autosome comparisons, some of these groups contain further genomic elements such as germline-restricted chromosomes that are maternally-inherited in gall midges and show paternally-biased inheritance in sciarid flies (Hodson and Ross 2021; Hodson et al 2021), enabling further within-genome comparisons.…”
Section: Discussionmentioning
confidence: 99%
“…Although some insects have numerous GRCs ( Hodson and Ross 2021) and the zebra finch GRC is the largest chromosome of its karyotype ( Pigozzi and Solari 1998) , genomic and transcriptomic data of these GRCs have been restricted to a 19-kb intergenic region of zebra finch GRCs until not so long ago ( Itoh et al 2009) . It is only recently that a wealth of sequencing data has provided first glimpses into the sequence content of GRCs of songbirds (Biederman et al 2018; Kinsella et al 2019; Torgasheva et al 2019; Pei et al 2021) and sciarid flies ( Hodson et al 2021) , revealing that GRCs contain many dozens to hundreds of genes and that they may have existed for millions of years in these lineages (Kinsella et al 2019; Hodson et al 2021) .…”
Section: Emerging Appreciation Of Diverse Forms Of Within-individual Genome Variationmentioning
confidence: 99%